The midnight farm - Lindbergh, Reeve; Jeffers, Susan (New York : Dial Books for Young Readers, 1987)
Secrets of the dark are revealed in this poem describing a farm at midnight.
Booklist Editors' (Reviewers') Choice
Bulletin Of The Center For Children's Books
Kirkus Reviews
2.5
K-3
Keywords: Night -- Juvenile poetry; Farm life -- Juvenile poetry; Children's poetry, American; Night -- Poetry; Farm life -- Poetry; American poetry; Night -- Poetry; Farm life -- Poetry; American poetry